Implementation of Religious Moderation in Tolerance Village in Bandung City - Pauzian, Muhamad Hilmi; Kuswana, Dadang; Hernawan, Wawan (Jurnal Iman dan Spiritualitas, 2024)
This research aims to understand and analyze the understanding of religious moderation and the manifestation of religious moderation in the Village of Tolerance, Kebon Jeruk sub-district, Andir District, Bandung City, Indonesia. This research uses Alfred Schutz's religious phenomenology approach regarding the construction of meaning, then analyzed using indicators of religious moderation, namely tolerance, non-violence and radicalism, national commitment and accommodating to local culture. The method used in this research is grounded research, a type of qualitative research with data collection techniques through observation, interviews and documentation. The data sources used in this research are primary and secondary. Primary sources were obtained from interviews with village officials, community leaders, religious leaders, and the people of Kampung Toleransi. Meanwhile, secondary data was obtained through books, journals and websites. The results of this research can be concluded that in the Village of Tolerance, there is a manifestation of religious moderation. Religious moderation is understood as an attitude or view that respects each other amidst existing differences. Having different views or beliefs is not a problem for the people of Kampung Toleransi, but with the differences that exist, each religious community always gives each other space to express their religion in a respectful, safe, comfortable and peaceful manner without any intimidation from other religious communities. The attitude of religious moderation in Tolerance Village can be seen from the people who have and always prioritize an attitude of tolerance, wasatiyah or balanced, fair, musawah or equal, and deliberation. Its manifestation is realized in the form of strengthening tolerance, national commitment, anti-violence and radicalism, respect for local culture, the role of religious figures and government policies.